PERTANGGUNG JAWABAN PIDANA TERHADAP PENGGUNAN JASA PROSTITUSI PADA MEDIA ONLINE - Dika Rahmat Nasution; Frans Simangunsong (Gapenas Publisher, 2023)
Technological developments have brought new changes in people's lives, not only having positive sides but also negative impacts including in the field of decency which has recently been rampant, such as prostitution, which was originally conventional to become online based. These actions can be said to be incompatible with the social values of society. The Indonesian government is not firm in prohibiting the practice of prostitution or in terms of criminal liability against users of prostitution services, this can be seen from the absence of regulations that can ensnare prostitution service users. The purpose of this study is to determine the regulation of criminal liability for prostitution service users in positive law. and efforts to criminalize prostitution service users in positive law in Indonesia. This research uses a descriptive normative juridical method. The result of the research is that the absence of criminal liability arrangements for prostitution service users makes these acts more prevalent. For that we need an effort to criminalize prostitution service users in positive law so that acts that are not in accordance with the values of the community can be processed legally